A new location record of European polecat (Mustela putorius L.) from northeastern forests in Turkey - Gündogdu, Ebubekir (Array, 2018)
The present study deals with European Polecat Mustela putorius found at one locality (near the Kop River in Bayburt) on the region of Eastern Black Sea of Turkey. This species are new records for the Northeastern Anatolia and the city of Bayburt. European polecat was previously reported from the region of Marmara, Trakya and Western Black Sea. The morphological and distributional features of this species are presented.